Thallium sorption and speciation in soils: Role of micaceous clay minerals and manganese oxides. (1st November 2020) - Wick, Silvan; Baeyens, Bart; Marques Fernandes, Maria; Göttlicher, Jörg; Fischer, Marlene; Pfenninger, Numa; Plötze, Michael; Voegelin, Andreas
Abstract: Sorption processes control the solubility of toxic thallium (Tl) in soils and thereby its potential leaching into groundwater or uptake by plants. Micaceous clay minerals and Mn oxides are considered to be key sorbents for Tl in soils. We studied the sorption and speciation of Tl in 36 geogenically Tl-rich topsoil materials from the Swiss Jura Mountains by combining chemical extractions, isotope exchange experiments, adsorption experiments, X-ray absorption spectroscopy (XAS), and sorption modelling. We demonstrate that the relation between exchangeable and soluble Tl determined in batch extractions of soils with only geogenic and with freshly spiked Tl matches adsorption isotherms of freshly spiked Tl, and that this relation can be described with a published 3-site cation exchange model for Tl adsorption onto illite. Complemented with XAS data, the results show that micaceous clay minerals control the short-term solubility of Tl via cation exchange, but also the long-term sequestration of most geogenic soil Tl (>90%) via structural fixation. Adsorption competition with K + and NH4 + at the frayed edges of micaceous clay minerals greatly affects Tl solubility. Increases in the dissolved concentrations of K and NH4 in soil pore water may therefore lead to the release of Tl into solution. The fractions of geogenic Tl associated with Mn oxides were about half as high as the fractions of exchangeable Tl. This Mn-associated Tl is not readily mobilized by cation exchange, but could be released during periodic water logging and soil reduction. In (periodically) reducing environments, the potential of Mn oxides for long-term Tl sequestration is therefore limited. In conclusion, the results from this study highlight the importance of micaceous clay minerals for Tl cycling in soils and sediments, and suggest that concepts developed to assess the sorption of (radio)caesium onto micaceous clay minerals in soils and sediments are transferable to Tl.